Occlusion of sight, sound and smell during Green Exercise influences mood, perceived exertion and heart rate. Issue 3 (3rd May 2016) - Wooller, John-James; Barton, Jo; Gladwell, Valerie F; Micklewright, Dominic
Abstract : This study's aim was to identify the relative contribution of sight, sound and smell to the Green Exercise effect. It was hypothesised that visual occlusion while exercising in a natural environment would have the greatest diminishing effect on perceived exertion and mood compared to auditory and olfactory occlusion. Twenty-nine healthy participants were randomly assigned to one of the three groups: visual ( n  = 10), auditory ( n  = 9) and olfactory occlusion ( n  = 10). Each performed six, 5-min bouts of exercise alternating between full sensory and occlusion. Rate of perceived exertion (RPE), heart rate (HR) and mood were recorded at the end of each bout. Sensory-occlusion increased mood, RPE and HR; effects were strongest when sounds were blocked but virtually absent when vision was blocked. During sensory occlusion, mood changes were characterised by increased Fatigue and Confusion, and reduced Vigour. Reductions in Tension and Vigour and increases in Fatigue were found during full sensory exercise, consistent with previous research findings.